The Coaching Model for Prospective Science and Mathematics Teachers from the Achievement and KIPK Paths - Parmin; Agus Yulianto; Eling Purwantoyo; Ibnul Mubarok; Iwan Junaedi (Universitas Pendidikan Ganesha, 2022)
Analysis of students' achievement in 2019 found new facts that there was a tendency to decrease in achievement from the achievement path and the Indonesian Smart College Card students. The percentage of students' achievement from both paths is less than 5%. This study aims to develop a student achievement coaching model for prospective science and mathematics teachers from the achievement and KIPK paths. The research uses research and development methods to develop a student coaching model involving education management experts to validate the model. The study obtained results where the student achievement coaching model was declared suitable for use by experts. The results of a large-scale model applicability test involve 240 prospective science and mathematics teachers. The percentage of students who made achievement for one semester from the achievement path was 16%, and from the KIPK path was 25%. The coaching model increased students' achievements, which was less than 5% for both paths. In conclusion, the student achievement coaching model from this research can be a new way to continue the culture to make achievements during school and college.